Bagaimana Literasi Matematis Siswa pada Penyelesaian Soal PISA-Like Berdasarkan Tingkat Kecerdasan Logis Matematis? - Elyasarikh, Annisa Alvi; Masriyah, Masriyah (MATHEdunesa, 2024)
Mathematical literacy refers to an individual's capacity to think mathematically to formulate, employ, and interpret solutions to real world problems that can be seen through PISA result. In solving PISA problems, one of intelligence that needed is mathematical logical intelligence. Therefore, this study intends to describe the mathematical literacy of students with high or low mathematical logical intelligence in solving PISA-Like problems. This study took a descriptive qualitative approach. The subjects of this research were 2 students with high or low logical intelligence. Data collection was carried out by logical mathematical intelligence test, PISA-Like test, and interviews. This research found that student that has a high level of logical intelligence was capable to explain what was known and asked about the problem, she was capable to design strategies to find mathematical solutions, she was capable to apply mathematical concepts by outlining the steps to find solutions to problems, she was capable to draw the conclusions obtained into the context of question, and she was capable of criticize the solutions to PISA-Like problems. Meanwhile, student that has a low level of mathematical logical intelligence was capable to identify what was known and asked about the problem, she was capable to draw the conclusions obtained into the context of question, but she was quite capable to design strategies to find mathematical solutions, she was quite capable to apply mathematical concepts by outlining the steps to find solutions to problems, and she was less capable to criticize the solutions to PISA-Like problems.